2015
DOI: 10.1093/pcp/pcv135
|View full text |Cite
|
Sign up to set email alerts
|

Red/Far Red Light Controls Arbuscular Mycorrhizal Colonization via Jasmonic Acid and Strigolactone Signaling

Abstract: Establishment of a nitrogen-fixing symbiosis between legumes and rhizobia not only requires sufficient photosynthate, but also the sensing of the ratio of red to far red (R/FR) light. Here, we show that R/FR light sensing also positively influences the arbuscular mycorrhizal (AM) symbiosis of a legume and a non-legume through jasmonic acid (JA) and strigolactone (SL) signaling. The level of AM colonization in high R/FR light-grown tomato and Lotus japonicus significantly increased compared with that determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
2
33
0
1
Order By: Relevance
“…Taken together, the combination of results strongly supports the possibility that JA in root exudates derived from high R/FR light-grown plants induced hyphal elongataion. In our previous study, 9 we showed that root exudates obtained from high R/FR-grown plants contained more strigolactone than exudates from low R/FR-grown plants. However, crude root exudates contain many compounds including amino acids, organic acids, sugars, phenolics, and other secondary metabolites.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Taken together, the combination of results strongly supports the possibility that JA in root exudates derived from high R/FR light-grown plants induced hyphal elongataion. In our previous study, 9 we showed that root exudates obtained from high R/FR-grown plants contained more strigolactone than exudates from low R/FR-grown plants. However, crude root exudates contain many compounds including amino acids, organic acids, sugars, phenolics, and other secondary metabolites.…”
mentioning
confidence: 70%
“…Earlier, we tried to measure the amounts of JA and JA derivatives directly from root exudates prepared from either high or low R/FR light-treated uninoculated plants. 9 However, even though exudates from 50 plants were analyzed by LC/MS, we could not definitely find any JA-related compounds, most likely due to their very low concentrations and the presence of impurities. Therefore, to evaluate JA and JA derivative content, we took an indirect approach and studied the expression levels of JAresponsive genes in WT MG20 plants treated with root exudates prepared from either high or low R/FR light-treated plants.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…In the shade avoidance syndrome, plants grow taller or bend toward the light to avoid shade through the action of phytochromes (Smith and Whitelam 1997). In shade avoidance in the case of root nodulation and mycorrhization, host plants suppress these interactions under suboptimal light conditions through the phytochrome system to avoid expending energy (Nagata et al 2015;Suzuki et al 2011). Therefore, we can consider inhibition of nodulation by light as one of several avoidance responses plants use to conserve energy in response to environmental stress.…”
Section: Discussionmentioning
confidence: 99%